2017
DOI: 10.14474/ptrs.2017.6.4.196
|View full text |Cite
|
Sign up to set email alerts
|

The passive stretching, massage, and muscle energy technique effects on range of motion, strength, and pressure pain threshold in musculoskeletal neck pain of young adults

Abstract: Objective: Musculoskeletal neck pain have many symptoms which include decreased range of motion (ROM) and muscle strength, and increased pain. However, the management methods are controversial. The purpose of this study was to examine the effects of three interventions on ROM, strength, and pressure pain threshold (PPT) with musculoskeletal neck pain. Design: Pretest-posttest design. Methods: Thirty subjects participated in this experiment. They were randomly assigned to thefollowing groups: passive stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Characteristics of included studies are summarized in Table 2 and Table 3 . We used 15 studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] to analyze the effects of MET in patients with non-specific acute neck pain, and 6 studies [ 49 , 50 , 51 , 52 , 53 , 54 ] to analyze the effects of MET in patients with non-specific chronic neck pain. Articles had sample sizes ranging from 28 to 90, contributing to a total sample size of 913 participants, consisting of 527 females and 386 males with a mean baseline age of 18 to 55 years with an average of 32.18 (±7.59).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of included studies are summarized in Table 2 and Table 3 . We used 15 studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] to analyze the effects of MET in patients with non-specific acute neck pain, and 6 studies [ 49 , 50 , 51 , 52 , 53 , 54 ] to analyze the effects of MET in patients with non-specific chronic neck pain. Articles had sample sizes ranging from 28 to 90, contributing to a total sample size of 913 participants, consisting of 527 females and 386 males with a mean baseline age of 18 to 55 years with an average of 32.18 (±7.59).…”
Section: Resultsmentioning
confidence: 99%
“…Three clinical trials were considered. Jeong et al [ 51 ] analyzed the impact of MET and passive stretching massage on ROM, strength, and pressure pain threshold (PPT) in patients with neck pain. They randomly assigned 30 subjects to three groups: Group 1 ( n = 10) received passive stretching, Group 2 ( n = 10) received massage, and Group 3 ( n = 10) received MET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stretching the musles around the neck and Original Article performing neck stabilization exercises (NSEs) are commonly used in the clinic as a method of solving cervical problems. Stretching stimulates the proprioceptive receptors by stretching the muscles and tendons, preventing muscle deterioration, removing fatigue substances, and improving elasticity of the entire muscle tissue [12,13]. Several previous studies have suggested that NSEs improve neck pain and deep muscle activity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have applied a number of methods to enhance flexibility, including massage, muscle energy techniques, myofascial release techniques, proprioceptive neuromuscular facilitation (PNF), and static stretching [1,5,6]. Stretching is necessary to manage muscle stiffness and maintain normal muscle length, and by stretching soft tissues such as muscles, tendons, ligaments, it increases joint range,…”
Section: Introductionmentioning
confidence: 99%